PENDIDIKAN PRA NIKAH BAGI CALON PENGANTIN DI KUA KECAMATAN SYAMTALIRA BAYU - Cut Sukma Keumala; T. Amiruddin (PENCERAHAN, 2018)
Religious Affairs Office provides premarital guidance to prospective married couples wishing to marry. KUA has been trying to optimally provide premarital counseling. Recently, however, this ahir premarital guidance given KUA against the couple almost ignored. This is evident from past guidance in KUA that only lasts 1-2 hours, and is still very minimal. This is the reason that can be expressed by the authors as background research, entitled "Education Pre marriage for bride at KUA District of Syamtalira Bayu." In preparation of this paper used the method of field research (field research), the research conducted directly into the field to obtain data and information. This type of research is qualitative descriptive approach, where the data obtained will be presented so that a description interrelated. Data were collected through observation, interviews, and documentation. The results of the study authors, among others, the implementation of pre-marital counseling is done in KUA Syamtalira Bayu generally not maximized. The period of pre-marital counseling at KUA Syamtalira ± Bayu lasted only 2 hours and is still very minimal, and not in accordance with the regulations set DG Bima Islam. Premarital guidance is an important effort undertaken KUA Syamtalira Bayu for the bride and groom as well as add to their stock of knowledge about the wedding. KUA Syamtalira Bayu has sought the implementation of premarital education, but still have weaknesses in the application.